2010
DOI: 10.1111/j.1474-919x.2010.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

The environmental impacts of biomass crops: use by birds of miscanthus in summer and winter in southwestern England

Abstract: We compared birds in a group of established and well-managed miscanthus (Miscanthus x giganteus) fields in Somerset and East Devon, southwestern England, with plots of short rotation coppice (SRC) willow, arable crops and grassland in two winters and one summer. Following early spring cutting, 19 miscanthus fields grew taller, initially produced greater cover and were less weedy than SRC. As stubble in May, the miscanthus contained broadly similar species at similar densities to arable and grassland comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…; Sage et al . ). With short‐rotation woody crops, the specific vegetative characteristics of cultivated species influenced nesting propensity for certain species of birds, and therefore, site and species‐specific guidelines will need to be developed in new areas (Verschuyl et al .…”
Section: Best Management Practices and On‐site Mitigationmentioning
confidence: 97%
See 1 more Smart Citation
“…; Sage et al . ). With short‐rotation woody crops, the specific vegetative characteristics of cultivated species influenced nesting propensity for certain species of birds, and therefore, site and species‐specific guidelines will need to be developed in new areas (Verschuyl et al .…”
Section: Best Management Practices and On‐site Mitigationmentioning
confidence: 97%
“…field margins or undisturbed grasslands; Semere & Slater ; Sage et al . ; Riffell et al . ; Robertson et al .…”
Section: Impacts Of Emerging Energy Sectors To Wildlifementioning
confidence: 99%
“…This was verified by the more severe decrease in fledgling numbers when the production of bioenergy increases, meaning that the breeding period is shortened and less breeding attempts will occur. However, previous field studies related to bird and bioenergy crops showed that miscanthus supports a higher density of breeding skylarks than other arable crops, but at an early stage of crop establishment when the vegetation does not exceed a maximum threshold (Bellamy et al, 2009;Sage et al, 2010;Semere and Slater, 2007). The high skylark density found in the literature was explained by a significant proportion of bare ground and the presence of weeds on which adults feed.…”
Section: Negative Effect Of Food and Bioenergy Production On Skylarksmentioning
confidence: 74%
“…In intensive agricultural landscapes Miscanthus fields may improve biodiversity due to the lack of tilling, reduced pesticide level and the provision of hiding places, especially during winter [13,54]. On the contrary, very few animals feed directly on Miscanthus and if the management of full grown Miscanthus fields becomes so successful that weeds are totally suppressed, and if fields become so large that field margins will constitute only a smaller fraction, the benefits will decrease [54,55].…”
Section: Risks Associated With Miscanthus Productionmentioning
confidence: 96%